MODEL MANAJEMEN RANTAI PASOK INDUSTRI PERIKANAN TANGKAP BERKELANJUTAN DI PROPINSI MALUKU (The Ideal Model of Supply Chain Management of Sustainability Industrial Capture fisheries in Maluku Province) - Siti Chairiyah Batubara; M. Syamsul Maarif; . Marimin; Hari Eko Irianto (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2017)
ABSTRACTDesigning and managing Industrial capture fisheries Supply Chain is complex and its faces socially bound uncertainties such as poor collaboration, communication and information sharing. Such complexity cannot be reduced through quantitative supply chain design and management techniques.Â  The aim of this study was design an industrial capture fisheries supply chain in Maluku Province using Soft System Methodology. Multi Dimensional Scaling (MDS)and SCOR was applied in analyzing situational conditions related to the sustainability and performance of industrial capture fisheries. Analysis on capture fisheries shows in less sustainable category (43.91)and Â the performance of both fishermen and company indicate an excellent and good grade. SSM analysis generated root definitions: Ministry of Marine Fisheries, Department of Marine, regional institution and stakeholder of the supply chain (O) realize the sustainable fishing industry and implementation of reliable activities in the fisheries sector and competitive globally (W) which integrates all the units along supply chain and coordinate the flow of materials, information and finance ranging from such aspects : production, downstream industries (handling and processing), up to marketing (T) of the Fishermen, industries processing (C) on the entire supply chain throughÂ  effective and efficient mechanism (E) as well as coordination both center and regional institution (A) related to quality and standardization of fishery products, distribution, infrastructure, data and information on fisheries (T)". The supply chain management of sustainable fishing industry model was developed by 20 activties. Improvement of Industrial capture fisheries supply chain in Maluku Province can be reached by doing activities within relevant system.Keywords: industrial capture fisheries, Multi Dimensional Scalling, SCOR, supply chain, SSM ABSTRAKMerancang manajemen rantai pasok industri perikanan tangkap merupakan hal yang kompleks. Penelitian ini bertujuan mendisain model manajemen rantai pasok industri perikanan tangkap yang ideal di Propinsi Maluku. Soft System Methodology (SSM) digunakan sebagai pendekatan kajian yang didukung oleh Multi Dimensional Scalling (MDS) untuk mengukur keberlanjutan industri perikanan tangkap dan Supply Chain Operation Reference(SCOR) untuk menganalisis kinerja industri perikanan tangkap.Â  Hasil penelitian menunjukkan bahwa keberlanjutan industri perikanan tangkap berada pada kategori kurang berkelanjutan dan kinerjanelayan dan perusahaan berada pada kategori sangat baik dan baik. Analisis SSM menghasilkan root definition â€œKementerian Kelautan Perikanan, Dinas Kelautan, PEMDA dan pelaku rantai pasok (O) mewujudkan industri perikanan tangkap yang berkelanjutan dan terselenggaranya aktivitasÂ  di sektor perikanan yang andal dan mempunyai daya saing secara global (W) yang mengintegrasikanÂ  semua unit dalam rantai pasok dan mengkoordinasikanÂ  aliran material, informasi dan keuangan mulai dari aspek produksi, industri hilir (handling dan processing), hingga ke pemasaran (T) dari para Nelayan, industri-industri pengolah (C) pada seluruh rantai pasokÂ  melalui mekanisme yang efektif dan efisien (E) serta koordinasi kelembagaan pusat dan daerah (A) terkait mutu dan standardisasi produk perikanan, distribusi, sarana prasarana, infrasrtuktur serta data dan informasi perikanan (T)â€. Model manajemen rantai pasok industri perikanan tangkap di Propinsi Maluku dibangun atas 20 aktivitas. Perbaikan rantai pasok industri perikanan tangkap dapat dicapai dengan melakukan aktivitas-aktivitas dalam model konseptual yang dibangun.Kata kunci: Â industri perikanan tangkap, Multi Dimensional Scalling, SCOR, rantai pasok,SSM